PRODUCTIVITY OF FIRST CALVING COWS UKRAINIAN BLACK-AND-WHITE DAIRY BREED DEPENDING ON WEIGHT GROWTH OF HEIFERS - A. A. Klymkovetskyi; Dmytro Nosevych (Тваринництво та технології харчових продуктів, 2020)
The productivity of cows with the first calving depending on live weight and average daily gains of heifers during rearing studied. The data of animals of Ukrainian Black-and- White dairy breed of Kyiv factory type used for the research. Every three months, from birth to 18 months of age, heifers were determined live weight and average daily gain. According to the indicators of weight growth, the heifers divided into 5 groups of the standard deviation principle from the mean. In animals included in these groups studied the performance of the first lactation. It found that obtaining a live weight of 3-month-old heifers over 127 kg can significantly reduce the age of the first calving. The advantage over animals belonging to the groups with less weight is 2.7-3.5 months. Increasing the live weight of heifers at 12 and 15 months also allows reducing the age of the first calving. Moderate (less than 722 g per day) growth of heifers at the age of 6-9 months also has a positive effect on the reduction of the age of the first calving. The weight of newborns heifers during lactation was associated with first calving cow’s milk yield. Heifers born with the lowest live weight (less than 28 kg) had after the first calving milk yield per lactation 145… 1956 kg more than in other groups. The live weight of 3-month-old heifers is of the greatest importance for the formation of high milk productivity of cows. Obtaining live weight of heifers of this age 117-127 kg with an average daily gain of 902-1037 g provided in first the lactation the largest milk yield with an advantage over animals of other groups up to 3119 kg. In older age periods, the influence of growing heifers on the formation of milk productivity is less pronounced, and the optimal live weight and growth rate was at the level of the average size of the herd. The research results can used to optimize the growth plans of heifers and their selection